2011
DOI: 10.1111/j.1751-9004.2010.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

The Köhler Group Motivation Gain: How to Motivate the ‘Weak Links’ in a Group

Abstract: A recurring question of successful group work is how to maintain high task motivation of the individual members. This paper reviews research on one well documented group motivation gain phenomenon, where group members are more highly motivated than comparable individual performers – the Köhler motivation gain effect. The basic effect is attributed to two psychological mechanisms, one involving upward social comparisons and a second involving the indispensability of group members’ efforts. In addition to summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 52 publications
1
86
0
Order By: Relevance
“…peddling an exercise bike). Second, unlike previous laboratory studies [13], Feltz et al [18] found that motivation gain was entirely due to social comparison-that is, making the task into a conjunctive group task did not boost effort above that level obtained with coacting but otherwise independent exercisers. They speculated that this may have been because their one-time exercise session was approached by their participants as an inherently competitive-not as a collaborative-task setting.…”
Section: Introductionmentioning
confidence: 44%
See 1 more Smart Citation
“…peddling an exercise bike). Second, unlike previous laboratory studies [13], Feltz et al [18] found that motivation gain was entirely due to social comparison-that is, making the task into a conjunctive group task did not boost effort above that level obtained with coacting but otherwise independent exercisers. They speculated that this may have been because their one-time exercise session was approached by their participants as an inherently competitive-not as a collaborative-task setting.…”
Section: Introductionmentioning
confidence: 44%
“…Considerable basic laboratory research has shown that having people work together at a task can, under the right conditions, reliably boost their task motivation [11,12]. The best documentation of such group motivation gains is the Köhler effect [13,14] -compared to working individually, the weaker member of the group tends to be more motivated when working together with a moderately more capable partner, especially when the group's final level of performance depends primarily upon the weaker member (i.e., when the group task has conjunctive task demands [15]. This motivation gain appears to arise from two processes-a tendency to strive to match or exceed the performance of one's more capable partner (via social comparison process [16]) and a tendency to work harder when the group's outcome (and/or one's evaluation by the group) hinges crucially on one's own level of effort (via an indispensability process) [17].…”
Section: Introductionmentioning
confidence: 99%
“…The Köhler effect literature points to a number of social contexts that can dramatically bolster task motivation, including the motivation to exercise. These include making one's efforts indispensible for collective success and one's evaluation in the group, making the group important, and making it easy for teammates to monitor and evaluate each others' performances continuously (see Kerr & Hertel, 2011). The present paper suggests that minimizing extrinsic incentives for exercising is yet another motivation-enhancing contextual feature.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the demands of the group task can be crucial; group tasks that make the least capable member's performance critical for group success (e.g., a mountain climbing team tethered together and able to climb at the speed of the slowest climber--what Steiner, 1972, called a conjunctive group task) generally results in the strongest Köhler effect (Hertel et al, 2008;Kerr et al, 2007). See Weber & Hertel (2008) for a meta-analytic or Kerr & Hertel (2011) for a narrative review of this literature.…”
Section: Incentives and The Köhler Group Motivation Gain Pagementioning
confidence: 99%
“…Most importantly, the demands of the group task can be crucial; group tasks that make the least capable member's performance critical for group success (e.g., a mountain climbing team tethered together and able to climb at the speed of the slowest climber--what Steiner, 1972, called a conjunctive group task) generally results in the strongest Köhler effect (Hertel et al, 2008; See Weber and Hertel (2007) for a meta-analytic or Kerr and Hertel (2011) for a narrative review of this literature.…”
Section: Group Dynamics and Motivation To Exercisementioning
confidence: 99%